EVALUASI HUBUNGAN PENDAPATAN ASLI DAERAH PROVINSI DAN KOTA: STUDI KASUS JAWA TIMUR-SURABAYA - Rahmawati, Azharina; Silvia Ayu Tri Octavia; Revienda Anita Fitrie; Eva Hany Fanida (Nusantara Hasana Journal, 2026)
This study aims to analyze the relationship of Regional Original Revenue (PAD) between the Provincial Government of East Java and the City Government of Surabaya within the framework of fiscal decentralization. This research uses a qualitative case study approach with secondary data from regional budget reports and official documents. The results show differences in fiscal structure and capacity between the two regions. East Java’s PAD is dominated by motor vehicle taxes, while Surabaya has a more diverse structure supported by the service and trade sectors. Surabaya demonstrates higher fiscal independence compared to the provincial government. However, fiscal disparities among regions in East Java still exist. The fiscal relationship between the province and the city is indirect and coordinative, indicating that fiscal decentralization has not been fully effective.